Towards a model of social innovation: cross-border learning processes in the context of an ageing society - Berit Skov Bjerregaard, Lene; Maciulskyte, Sonata; Acienė, Elvyra; Christensen, Jonas (Social Welfare: Interdisciplinary Approach, 2018)
The aim of this paper is to reveal how the collaboration process mobilise resources among countries with different logics of welfare, yet address similar problems of ageing society, i a caring, a learning and a political perspective.The study draws on social science theories and the analysis is based on qualitative empirical data from an interdisciplinary field.The main conclusion is that a multi-dimensional understanding of dementia care by shared knowledge of different welfare logics adds value to experiences of cross-border learning.  A social innovation model is presented.
Keywords: Interdiciplinarity; ageing society; social innovation; cross-border; collaboration; community of learning and practices; networking